The impact of active community-based survey on dementia detection ratio in Taiwan: A cohort study with historical control - Lu, Yun-Ru; Wu, Tzy-Haw; Jeng, Yachung; Lee, Wen-Yuan; Hsu, Wei-Chih; Yen, Amy Ming-Fang; Pan, Shin-Liang; Chen, Yen-Ching; Chen, Sam Li-Sheng; Chen, Hsiu-Hsi; Liou, Horng-Huei (Frontiers in Public Health, 2023)
Background Although early dementia detection is crucial to optimize the treatment outcomes and the management of associated symptoms, the published literature is scarce regarding the effectiveness of active screening protocols in enhancing dementia awareness and increasing the rate of early detection. The present study compared the detection ratio of an active community-based survey for dementia detection with the detection ratio of passive screening during routine clinical practice. Data for passive screening were obtained from the National Health Insurance (NHI) system, which was prospectively collected during the period from 2000 to 2003. Design A population-based cohort study with historical control. Setting Taiwan. Participants A total of 183 participants aged 65 years or older were involved in a community-based survey. Data from 1,921,308 subjects aged 65 years or older were retrieved from the NHI system. Measurements An adjusted detection ratio, defined as a ratio of dementia prevalence to incidence was used. Results The results showed that the dementia prevalence during the 2000–2003 period was 2.91% in the elderly population, compared with a prevalence of 6.59% when the active survey was conducted. The incidence of dementia in the active survey cohort was 1.83%. Overall, the dementia detection ratio was higher using active surveys [4.23, 95% confidence interval (CI): 2.68–6.69] than using passive detection (1.45, 95% CI: 1.43–1.47) for those aged 65–79 years. Similar findings were observed for those aged 80 years and older. Conclusion The implementation of an active community-based survey led to a 3-fold increase in the detection rate of early dementia detection compared to passive screening during routine practice.